Two new species of Lepidiella Enderlein, 1937 (Diptera: Psychodidae) from the Neotropical Region with taxonomic comments about the species of the genus - Araújo, Maíra Xavier; Bravo, Freddy (Zootaxa, 2019)
Lepidiella Enderlein, 1937 is a Neotropical genus with 15 species. This paper describes two new species from Brazil, Lepidiella maculosa sp. nov. and Lepidiella wagneri sp. nov., and provides an identification key for males of the genus.